The evolution of methods for urinary steroid metabolomics in clinical investigations particularly in childhood. Issue 181 (July 2018) - Honour, John W.; Conway, E.; Hodkinson, R.; Lam, F.
Highlights: A review of urinary steroid profiling from sample collection, processing and analysis. Examine the progression from GC–MS to LC–MS/MS and GC–MS/MS. Provide reference ranges for steroid excretion rates as a benchmark for others. Describe evolution of methods for analysis of free steroids to intact conjugated forms. Abstract: The metabolites of cortisol, and the intermediates in the pathways from cholesterol to cortisol and the adrenal sex steroids can be analysed in a single separation of steroids by gas chromatography (GC) coupled to MS to give a urinary steroid profile (USP). Steroids individually and in profile are now commonly measured in plasma by liquid chromatography (LC) coupled with MS/MS. The steroid conjugates in urine can be determined after hydrolysis and derivative formation and for the first time without hydrolysis using GC–MS, GC–MS/MS and liquid chromatography with mass spectrometry (LC–MS/MS). The evolution of the technology, practicalities and clinical applications are examined in this review. The patterns and quantities of steroids changes through childhood. Information can be obtained on production rates, from which children with steroid excess and deficiency states can be recognised when presenting with obesity, adrenarche, adrenal suppression, hypertension, adrenal tumours, intersex condition and early puberty, as examples. Genetic defects in steroid production and action can be detected by abnormalities from the GC–MS of steroids in urine. New mechanisms of steroid synthesis and metabolism have been recognised through steroid profiling. GC with tandem mass spectrometry (GC–MS/MS) has been used for the tentative identification of unknown steroids in urine from newborn infants with congenital adrenal hyperplasia. Suggestions are made as to areas for future research and for future applications of steroid profiling. As routine hospital laboratories become more familiar with the problems of chromatographic and MS analysis they can consider steroid profiling in their test repertoire although with LC–MS/MS of urinary steroids this is unlikely to become a routine test because of the availability, cost and purity of the internal standards and the complexity of data interpretation. Steroid profiling with quantitative analysis by mass spectrometry (MS) after chromatography now provides the most versatile of tests of adrenal function in childhood.